2020
DOI: 10.3390/atmos11090974
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Passive Green Technologies on the Microclimate of Historic Urban Structures: The Case Study of Lodz

Abstract: Rapid population growth necessitates modifications of urban form, especially in city centers. Consequently, the correlation of the outdoor environment with the occupant’s behavior has profoundly changed. In this study, the authors describe a method, that allows for the estimation of the impact of passive green technologies on the microclimate of historic urban structures, taking into account the city-specific conditions. The Envi-met application, which is widely applied in urban climatology, was used to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The results of the study of microclimatic conditions in the immediate vicinity of the building were also promising. The maximum reduction in air temperature was 0.37°C at the southern facade, and 0.21°C at the eastern façade (in comparison to similar studies, such a result is comparable and significant [13]). Additionally, the conducted analyses showed that the value of the daily air temperature amplitude in the green area was lower by 2.05°C in relation to the area of the asphalt street.…”
Section: Summary -Assessment Of the Adopted Planning Solutions' Impac...supporting
confidence: 69%
See 1 more Smart Citation
“…The results of the study of microclimatic conditions in the immediate vicinity of the building were also promising. The maximum reduction in air temperature was 0.37°C at the southern facade, and 0.21°C at the eastern façade (in comparison to similar studies, such a result is comparable and significant [13]). Additionally, the conducted analyses showed that the value of the daily air temperature amplitude in the green area was lower by 2.05°C in relation to the area of the asphalt street.…”
Section: Summary -Assessment Of the Adopted Planning Solutions' Impac...supporting
confidence: 69%
“…The following meteorological data were taken into account: air temperature, average radiation temperature, air humidity and wind speed. Information on human physical parameters, thermal insulation of clothing, as well 3 More at: [13].…”
Section: Thermal Comfortmentioning
confidence: 99%
“…It should be noted that the tool is considered efficient when performing studies for highly urbanized areas [30][31][32]. In addition, the authors' studies confirm that there is a possibility to use the application in climate studies of urban areas [33][34][35].…”
mentioning
confidence: 83%
“…This was possible by applying a modified version of logarithmic formula [37] and the relation proposed by Simiu [38]. The method was described in [35].…”
Section: Simulations Of Meteorological Parametersmentioning
confidence: 99%
“…Incorporating climate modelling into urban and open space planning brings also the possibility to test different green climate adaptation measures, as is demonstrated in several studies (e.g., [24,25]). Yet, many studies are conducted at the microscale with ENVI-Met (e.g., [26][27][28]), while studies at the mesoscale often do not deliver the detailed information necessary for urban planning (for example, the CLARITY CSIS platform [29]). This contribution offers an example of a climate-responsive approach in which we describe a multidisciplinary and interscalar design process combining fields of knowledge bridging urban climatology, landscape planning, and governance.…”
Section: Introductionmentioning
confidence: 99%